Environmental Taxation and Economic Growth in Africa: A Macroeconomic Panel Data Analysis - Ouchouid, Iyman; El Alaoui, Aicha (International Journal of Economics and Financial Issues, 2025)
Environmental taxation is increasingly recognized as a key tool for achieving sustainable development goals. The Rio Convention (1992), the Kyoto Protocol (1997) and the Paris Agreement (2015) demonstrate the growing global commitment to addressing climate change. These milestones underscore a growing awareness of environmental issues and have encouraged the gradual integration of ecological policies worldwide. In Africa, where environmental and economic challenges are closely interlinked, implementing tax policies that reduce negative environmental impacts while promoting economic growth is crucial. This study examines the impact of environmental taxation on economic growth in Africa and explores how economic growth can be achieved while taking environmental issues into consideration. This paper explores the relationship between environmental taxation and economic growth in Africa between 2000 and 2020 through an econometric analysis of panel data from five African countries: Morocco, Cameroon, South Africa, Niger and Tunisia. Our results show a negative and statistically significant relationship at the 5% level between environmental tax revenues and the growth rate of gross domestic product (GDP). For each one-unit increase in environmental tax revenue as a proportion of total tax revenue, the GDP growth rate decreases by 0.167 units, all else being equal.